ANALISIS KOINTEGRASI DAN KAUSALITAS ANTARA INFRASTRUKTUR JALAN, PERDAGANGAN BARANG DAN PERTUMBUHAN EKONOMI DI NEGARA ANGGOTA ASEAN - Antonius KAP Simbolon (Quantitative Economics Journal, 2018)
This research aims to analyze Cointegration and Causality among ASEAN Road Infrastructure, ASEAN Total Trade in Goods and Rate of GDP Growth, using time series data, that is yearly data during the time period 2007 to 2015. The method used to test cointegration is Johansen’s Multivariate Cointegration Test dan the method used to test the causality is Granger’s Causality. The result of cointegration test revealed that there are a long run relationship between ASEAN Road Infrastructure, ASEAN Total Trade in Goods and Rate of GDP Growth in each member country of ASEAN. While the results of the Granger Causality test found there is a two-way relationship (mutual causality) between ASEAN Total Trade in Goods and Rate of GDP Growth in each member country of ASEAN. But, there is one-way relationship between ASEAN Road Infrastructure and ASEAN Total Trade in Goods and Rate of GDP Growth in each member country of ASEAN, which ASEAN Road Infrastructure gives effect to ASEAN Total Trade in Goods and Rate of GDP Growth